Robust controller design of a wheelchair mobile via LMI approach to SPR systems with feedback output - Rossini, F. L.; Gaino, R.; Teixeira, M. C. M. [UNESP]; Assunção, E. [UNESP]; Cardim, R. [UNESP]; Covacic, M. R. (Ieee-inst Electrical Electronics Engineers Inc, 2015)
This article discusses the design of robust controller applied to Wheelchair Furniture via Linear Matrix Inequalities (LMI), to obtain Strictly Positive Real (SPR) systems. The contributions of this work were the choice of a mathematical model for wheelchair: mobile with uncertainty about the position of the center of gravity (CG), the decoupling of the kinematic and dynamical systems, linearization of the models, the headquarters building of parametric uncertainties, the proposal of the control loop and control law with a specified decay rate.
Keywords: Robust controller; Wheelchair furniture; Decoupling of systems; Control loop; LMI